Rainfall trends over 40 years in the Cobres River basin, Portugal: variability and impacts. - Silva, R M (2015)
Climate change is the most important topic in climatic research of the last few decades around the world. Global warming, and therefore changes in annual precipitation, has attracted the attention of the researchers in different regions of the world. One of the most significant consequences of the identified global warming would be an increase or decreasing in the magnitude and frequency of annual precipitation generated (Santos and Morais, 2013). Changes in annual precipitation have been identified in many studies conducted at local, regional or global scales (Silva et al., 2013). The main objective of this study is to analysis of the trends in annual precipitations at a regional scale over 40 years (1960–2000) in the Cobres River basin, southern of Portugal (37°28′ N–37°57′ N, 8°10′ W–7°51′ W), using statistical tools. This region is a semi-arid typical basin, middle-sized with area of 1194 km², located in the Alentejo province, an area suffering from desertification. It is a region of relatively low relief, with the elevation varying from 103 to 308 m above sea level. The climate in this region is characteristically Mediterranean and Continental, with moderate winters and hot and dry summers, high daily temperature range, and a weak and irregular precipitation regime; mean annual precipitation of rain gauge stations in the region varies between 400 and 900 mm, with around 50 to 80 rainy days per year.